THE APPLICATION OF SPECTRAL CT IN THE EVALUATION OF CORONARY ARTERY DISEASE AT THONG NHAT HOSPITAL – HO CHI MINH CITY - Nguyên Thuận, Huỳnh; Nguyên, Đỗ Võ Công; Tâm, Bùi Thị Thanh; Hậu, Trần Thị; Thành, Nguyễn Chí; Thị Mỹ Trang, Nguyễn; Khang, Trần An; Phong, Trần Thanh (Journal of Health and Aging, 2026)
At Thong Nhat Hospital, Ho Chi Minh City, the spectral CT system has brought significant advancements in the diagnosis of coronary artery disease. The post-processing applications of spectral CT that are used include: virtual monoenergetic images (MonoE), effective atomic number (Z-effective), iodine density map, iodine no water, virtual non-contrast images (VNC), and enhanced visualization of contrast-enhancing structures. The diverse types of images obtained from the spectral CT technique bring many benefits such as reducing the contrast media dose for patients and reducing artifacts to improve image quality, thereby helping to more accurately assess the degree of coronary stenosis. Iodine maps also help assess myocardial perfusion status, providing more comprehensive and accurate information about coronary artery disease. The use of VNC to calculate the calcium score as a replacement for true non-contrast (TNC) images is currently in the research phase at Thong Nhat Hospital with promising initial results, holding the promise of replacing TNC in CS assessment, thereby reducing the radiation dose for patients. This article aims to present the applications of spectral CT and actual clinical cases at Thong Nhat Hospital - Ho Chi Minh City to clarify the application of spectral CT in the evaluation of coronary artery disease.
Keywords: Coronary CT angiography; spectral CT; virtual non-contrast images .